Ketahanan Ekonomi dalam Kesultanan Utsmaniyah: Pelajaran bagi Krisis Ekonomi Modern - Alyaditha, Nachda; Rosmah, Rosmah; Parakkasi, Idris; Sudirman, Sudirman (Lembaga Yasin AlSys, 2025)
Islamic economic thought during the Ottoman Empire reflects the application of Islamic principles in the management of the state’s economy, with a focus on social welfare, equitable wealth distribution, and the regulation of natural resources. During this period, the economic system applied not only covered financial aspects but also societal welfare through practices such as waqf and zakat. Waqf was used to finance various social institutions such as schools, hospitals, and mosques, while zakat played a role in reducing economic disparities. The Ottoman state also regulated markets and trade to maintain economic stability and prevent exploitation that could harm the public. Islamic economic thought in this era emphasized the state’s role in achieving general welfare through fair and sustainable policies in accordance with Sharia principles. Overall, Islamic economic thought during the Ottoman period serves as a concrete example of an economy based on Islamic values aimed at achieving justice and collective well-being.